(untitled) (PANGEEA, 2025)
After the second world war, at one time with the anticipation of nuclear fission importance, the radioactive elements were “rediscovered” and became very important energy sources. In this time was elaborated a lot of studies about the radiation properties, but this study are not accessible for commoners, therefore existing very much exaggerated information about the impact of radiations in to environment. These study presence, in a common language, the theoretical aspects of radiations and, in final, some dates about the Chernobyl accident and the possible sources of supplementary irradiation in the Alba district, Romania.